ERROR ANALYSIS OF PROSPECTIVE MATHEMATICS TEACHER IN SOLVING ADDITIONAL AND MULTIPLICATION RULES PROBLEM IN COMBINATORICS BASED ON ADVERSITY QUOTIENT - Friska Mahatri; jeri araiku; Weni Dwi Pratiwi; Muhammad Yusup (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The background of this research is that there are still many prospective teacher students who still experience difficulties in solving addition and multiplication rules in combinatorics. This research is a qualitative descriptive research that aims to find out the mistakes of prospective teacher students in solving addition and multiplication rules in combinatorics based on adversity quitient. The research subjects were student teacher candidates in the 3rd semester of Mathematics Education, Faculty of Teaching and Education, Sriwijaya University. There are stages for this research including 1) preparation stage, 2) implementation stage, 3) final stage. Data collection was in the form of questionnaires and written tests. The results of the study were that student teacher candidates who had a Quitter type adversity quotient had 0 student teacher candidates with a percentage of 0%, Camper type adversity quotient had 58 student teacher candidates with a percentage of 82.86%, Climber type adversity quotient had 12 student teacher candidates with a percentage of 17 .14%. As well as prospective teacher students in the Adversity quotient category of the Climber type, they made 4 mistakes according to Newman's procedure, namely Comprehension Error, Transformation Error, Process Skill Error and Encoding Error. Student teacher candidates in the adversity quotient category of Camperr type made 5 mistakes according to Newman's procedure, namely Reading Errors, Comprehension Errors, Transformation Errors, Process Skill Errors and Encoding Errors.